Analysis of groundwater recovery and its effects on substructures in Bangkok{u2019}s aquifer system - Krit Saowiang; Pham, Huy Giao; Noppadol Phien-Wej; Kunnawee Kanitpong; Suttisak Soralump; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
1990s groundwater levels in the Bangkok aquifer system have gradually recovered, mainly due to strict control measures of groundwater extraction and the increased surface water supply. What effects such a groundwater recovery can impact on the compression characteristics of the soil layers, how is the soil rebound and possible instability of substructures constructed during the drying period, how the replenishment of the aquifers could be done etc. all of these questions need to be answered and as there are still very few on the problem of Bangkok groundwater recovery and its associated adverse geotechnical effects this study was proposed. This dissertation is a comprehensive study dealing with the analysis of groundwater recovery and its effects on substructures in the Bangkok aquifer system to understand better subsurface deformation and the risk of groundwater recovery {u2013} induced damage to substructures. Key factors affecting to substructures stability and subsurface deformation are geotechnical characterization of Bangkok clay, groundwater level change in PD aquifer and types of substructures. The subsurface deformation and substructures stability are influenced by pore water pressure distribution, effective stress, undrained shear strength in clay layers and type of substructures. The dissertation is structured in seven chapters, and namely, Chapter I explains on the rationale for the study and outlines the objectives and scopes of the study as well as its limitation. This study will focus on the effects of the groundwater recovery on the substructures in the uppermost 100-m zone of the Bangkok aquifer system only; Chapter II provides with a comprehensive overview of cities in the world that have experienced groundwater recovery as well as the current situations of Bangkok land subsidence and groundwater recovery; Chapter III outlines the methodology of the study, focusing on how to perform soil testing and characterization, groundwater modelling and numerical analysis of land deformation due to groundwater level changes as well as their effects on pile capacity; the next chapters from IV to VII present the main outputs of the study, e.g., Chapter IV presents a detailed soil characterization based on geotechnical testing results at six testing sites and a new comprehensive analysis of intrinsic compression behavior of Bangkok clays (i.e., soft. medium, stiff and hard clays). The results of this chapter will be used further as input data for groundwater and soil models to be performed in the next chapters; Chapter V presents the results of a three-dimensional groundwater modeling by MODLFOW that makes use of a comprehensive subsurface database provided by the groundwater resources department of Thailand (DGR). As a particular objective, the groundwater modeling aims to explain on how natural recharge has contributed to groundwater recovery of Bangkok aquifer system and helps to understand the current pictures of groundwater levels in the main aquifers; Chapter VI presents the results of Abaqus-based numerical analysis of subsurface deformation and possible effects on substructures due to groundwater recovery in Bangkok area and vicinities. Finally, Chapter VII provides with the major conclusions and recommendations that could be drawn from this study. In the following a more detailed description of the outputs obtained by this dissertation is given. The geotechnical characterization and groundwater data were collected to serve the a comprehensive analysis. The geotechnical data and groundwater level data were obtained from three testing areas in the Northern, Middle and Southern parts of Bangkok area. Two study sites in the Northern Part namely Chatuchak Park (TS1) and Kasetsart University (TS6); two study sites in the Middle Part namely SnamSua Pa (TS3) and Rommaninat park (TS4); and two study sites in the Southern Part namely Lumpini Park (TS2) and Ratchamangala University of Technology Krungthep (TS5). The intrinsic compression behavior of Bangkok clays was studied to links with parameters of the MCC model that use in the subsurface deformation analysis. The oedometer compression curves of soft, stiff and hard clay are plotted relative to ICL and SCL to understand the compression behavior of soft, stiff and hard clays. The in-situ stress state was plotted to understand better of natural state of Bangkok clay. A comprehensive, groundwater model was constructed by using the DGR database and run by using Visual MODFLOW with Visual MODFLOW Flex user interface to prediction the rate of groundwater recovery in the regional area of PD aquifer. The modeled domain with a size of 122x140 km2 and 385 m in depth. The grid in study areas is 1 km x 1 km. The total number of model grid in study area is 170,800 and consists of 140 rows x 122 columns. The surface and bottom elevations of 10 layers were used in the model consist 5 aquifers included BK, PD, NL, NB, and SK aquifers. For the last three aquifers were neglected because not many observation wells in theses aquifers and this study focus on the uppermost 100m. All the aquifers are assigned as the confined aquifer except the Bangkok aquifer that is considered as the unconfined aquifer. The pumping observation wells are 6,155 and 93 wells respectively were used in model to calibration. The hydraulic properties were calibrated by comparing the calculated and observed from 2001 to 2009. As a result, the behavior of groundwater recovery in Bangkok divided for three periods. Period I: from 2001 to 2003, the storage-in higher than storage-out with increasing rate implies that groundwater level drawdown and the pumping effect still exists.
Period II: from 2003 to 2005, when more water come into the aquifer and the pumping rate is decreased, the storage-in is still higher than storage-out, but pumping rate keep decreasing. Period III: from 2005 to 2010, the storage-in is constant due to stop pumping in Bangkok area and the rate of pumping outside Bangkok also decreased. The storage-out increases and crossed the storage-in in 2008, which implies that groundwater in the aquifers recovered. The rate of groundwater recovery in PD aquifer equal to 1-1.2m/year, 0.98m/year and 0.84m/year in the Northern, Middle and Southern parts respectively. These results are closed to observed data and used for subsoil deformation and substructures stability analysis. The comprehensive studies on geotechnical characterization, rate of groundwater recovery in PD aquifer with field monitoring and groundwater model lead to more comprehensive study on subsurface deformation analysis performed using a fully-coupled 2D plain strain FEM and MCC model by ABAQUS. This technique has been developed to analysis of pore pressure, effective stress change and subsurface deformation due to groundwater level change in aquifer were successful. The analysis was conducted for Northern, Middle and Southern parts. The change of groundwater level with time from groundwater modeling or observed data used as a transient pore pressure boundary condition in the model to predict the pore pressure distribution and effective stress in the upper soil layers and subsurface deformation,. The main simulation results are the cumulative surface deformation due to groundwater drawdown from 1960 to 1997, and groundwater recovery from 1997 to 2016. The calculated surface deformations are compared with surface settlement measurements from 1978 to 2011. In the Northern part, the measured surface settlement is about 80cm, while the calculated surface deformation in 2011 is 18 cm, or 22.5% of the measured value. For the Middle part, the measured surface settlement is about 50-60 cm, while the calculated surface deformation in 2011 is 27 cm or 45-54% of the measured value. For the Southern part, the measured surface settlement is about 60-70 cm, while the calculated surface deformation in 2011 is 36.8 cm or 52.6-64.7% of the measured value. The results of the fully coupled 2D are very helpful to assess the effects on substructures due to groundwater level change in PD aquifer. The pore pressure and effective stress change were used. Then the undrained shear strength of clay layers was calculated by using correlation between effective stress and undrianed shear strength from triaxial test. The effect on ultimate pile capacity was study. Most of the 20-40 story buildings are located in the Southern part, having the bored pile foundation of 1.2 and 1.5 m diameter and about 50-m length. Change in these ultimate pile capacity with time was predicted. The increasing and decreasing rates of ultimate piles capacity are 1.40 and 1.46 % per year for pile diameter of 1.2 and 1.5 m, corresponding to the drawdown and recovery periods, respectively. For low rise buildings, most of which are lower than 10-story and are supported on driven square pile foundation, i.e., 0.3x0.3m, 0.35x0.35m or I-pile foundation, i.e., 0.3x0.3, 0.35x0.35m. The pile tips rest on stiff clay or first sand layer at around 20-25m deep. The change in the ultimate piles capacity of a driven square pile of 0.3x0.3m, 0.35x0.35m and the 25m length was calculated. The increasing rate of ultimate piles capacity are 1.56 and 1.61% per year, respectively, while the decreasing rate of ultimate piles capacity are 1.40 and 1.45% per year, corresponding to the drawdown and recovery periods, respectively. For another case with the driven I-piles of 0.3x0.3 m, 0.35x0.35m, and 25 m lengths the increasing rate of ultimate piles capacity are 1.45 and 1.48% per year, while the decreasing rate of ultimate piles capacity are 1.26 and 1.30% per year, respectively. The ancient and old buildings, mostly found in the inner core area of Bangkok city, are on the shallow foundation and wooden piles of short length from 6 to 10 m, installed mainly in the soft to medium clay layers. As the increase in pore pressure in the soft to medium clay layers are still insignificant one can say that the ongoing recovery of groundwater levels in the PD aquifer has not yet affected the shallow foundations. The same can be said for basements and tunnels that are also located in the soft to medium clay layers. The study results showed that the combined of the comprehensive studies on geotechnical characterization, groundwater modeling and monitoring and the fully-coupled 2D FEM analyses provided a useful tool to understand the current situation of Bangkok groundwater, the associated land deformation and substructures stability in Bangkok area.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Geotechnical and Earth Resources Engineering
Thesis (Ph.D.) - Asian Institute of Technology, 2020
Keywords: Groundwater -- Thailand -- Bangkok; Aquifers -- Thailand -- Bangkok